Advanced hemodynamic monitoring during fetal surgery. (February 2016) - Saracoglu, Ayten; Saracoglu, Kemal Tolga; Schuerg, Rainer; Kafali, Haluk
Abstract: Fetal surgery is performed in several different fetal diagnosis centers with increasing frequency. Continuous tocolytic medication and effects of inhaled anesthetics on parasympathetic reflex vasodilation constitute a challenge for uteroplacental blood perfusion. The stability of pulmonary gas exchange and maternal hemodynamics is important. Otherwise maternal pulmonary oedema may easily occur according to an increase in pulmonary vascular permeability and extravascular lung water. Fluid management is required to ensure the continuity of the uteroplacental circulation and has to be performed very carefully. Hemodynamic monitoring parameters show us the principles of fluid management and allow us to draw a road map. In this review we aimed to present a summary concerning advanced hemodynamic monitoring during fetal surgery. Highlights: Advanced hemodynamic monitoring is essential for maternal cardiopulmonary function in patients undergoing fetal intervention. Significant amount of fluid may be absorbed into maternal circulation during fetal interventions. Fluid management is required to ensure the continuity of the uteroplacental circulation. The decision for fluid management should be given by the parameters of hemodynamic monitoring. Central venous pressure is not always enough to determine fluid response and deficit.